2021
DOI: 10.1001/jamaoncol.2020.6778
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of SARS-CoV-2 Infection Among Patients Undergoing Active Antitumor Treatment in Italy

Abstract: Role of the Funder/Sponsor: CDC staff had a role in the design and conduct of the project and collection and management of data in this project as part of the funding support and technical assistance given to state central cancer registries that participate in NPCR. The analysis and interpretation of the data; preparation, review, or approval of the manuscript; and decision to submit the manuscript for publication was the sole responsibility of the authors. Disclaimer:The findings and conclusions are those of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 3 publications
0
27
0
Order By: Relevance
“…Even when different types of cancers were correlated with COVID-19 mortality, NEN cases were not reported 16 . In one of the largest investigation of SARS-CoV-2 in patients with cancer which was the first focused specifically on patients receiving antitumor treatment, among around 60,000 cancer patients analyzed, no NEN were reported 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Even when different types of cancers were correlated with COVID-19 mortality, NEN cases were not reported 16 . In one of the largest investigation of SARS-CoV-2 in patients with cancer which was the first focused specifically on patients receiving antitumor treatment, among around 60,000 cancer patients analyzed, no NEN were reported 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 shows the PRISMA flow chart for the study screening and selection process in this research. Twenty-three trials including 19 retrospective studies [21] , [23] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] and 4 prospective studies [22] , [42] , [43] , [44] , enrolling 117735 study subjects ultimately met our criteria ( Figure 1 ). Six studies were performed in USA [25] , [26] , [29] , [31] , [35] , [40] , five in Italy [27] , [28] , [38] , [39] , [42] , four in Spain [27] , [36] , [37] , [43] , three in United Kingdom [22] , [33] , [34] , two in China [23] , [30] , one in France [41] , one in India [32] and one in Australia [21] .…”
Section: Resultsmentioning
confidence: 99%
“…Many studies demonstrated a higher risk of infection and developing complications in people with malignancies [ 1 , 16 , 17 ], while others [ 3 , 5 ] showed a similar incidence of SARS-CoV-2 between people with tumors and healthcare operators. Focusing on Italian real-life experiences, a large study from Aschele et al [ 18 ] who analyzed 59,989 patients from 118 Medical Oncology Units all over Italy between 15 January and 4 May 2020, recorded a 0.68% infection rate among active treatment patients with 77% of them being hospitalized. Bertuzzi et al [ 19 ] reported a 1.8% COVID-19 incidence rate (17/1267); SARS-CoV-2 infected patients required hospitalization in 82% of cases (14/17) with a 29% fatality rate.…”
Section: Discussionmentioning
confidence: 99%